FTY720/fingolimod, an oral S1PR modulator, mitigates radiation induced cognitive deficits. (29th September 2017) - Stessin, Alexander M.; Banu, Matei A.; Clausi, Mariano Guardia; Berry, Nicholas; Boockvar, John A.; Ryu, Samuel
Highlights: The current study provides a rationale for testing FTY720/Fingolimod as a mitigator of neurocognitive deficits in patients undergoing brain radiation therapy. Our results also suggest that Fingolimod can exert inhibitory effects on intracranial tumor growth – This is first clinically relevant example of a two-pronged approach where a mitigator of radiotoxicity simultaneously serves as a cancer therapeutic. Abstract: Purpose: This study evaluates FTY720/Fingolimod, modulator of sphingosine-1-phosphate (S1P) receptor, as a potential mitigator of radiation-induced neurocognitive dysfunction. Methods and materials: To study radiation-induced neurocognitive deficits, 6 week-old C57/Bl/6J mice received 0 or 7 Gy cranial irradiation and were treated with FTY720 or vehicle for seven weeks. Fear conditioning and Morris water maze were then employed to test learning and memory. Immunohistochemical staining for neural progenitor cells (NPCs) and mature neurons was used to assess changes in hippocampal neurogenesis. To test effects on tumor growth, mice harboring brain tumor xenografts were treated with FTY720 or vehicle for six weeks. Results: In irradiated mice, learning deficits were manifested by significantly longer latency times in the Morris Water Maze compared to non-irradiated controls (p = 0.001). The deficits were fully restored by FTY720. In irradiated brains, FTY720 maintained the cytoarchitecture of the dentate gyrus granular cell layer and partially restored the pool of NPC. In mice harboring brain tumor stem cell (BTSC) xenografts FTY720 delayed tumor growth and improved survival (p = 0.012). Conclusions: FTY720 mitigates radiation-induced learning dysfunction. A partial restoration of neurogenesis was observed. Furthermore, FTY720 appears to delay tumor growth and improve survival in a xenograft glioma mouse model.